Parâmetros genéticos para caracteres de crescimento, de produção e tecnológicos da madeira em clones de Eucalyptus spp - Tolfo, Ana Lídia Tonani [UNESP]; De Paula, Rinaldo Cesar [UNESP]; Bonine, Cesar Augusto Valencise; Bassa, Alexandre; Do Valle, Celina Ferraz (My University, 2005)
This work had to objectives to estimate genetic parameters of growth, yield and technological wood characters in 25 Eucalyptus spp. clones, at 80 months old. The experiment was disposed in the randomized blocks design with 50 clones and six repetitions of 10 plants. In three trees of 25 best clones to silvicultural traits, were evaluated genetics parameters for growth, yield and wood technological characters. Only viscosity of pulp it was not verified genetics variations among clones. The heritability estimates, evidencing the good genetic control about the characters analyzed and the possibility of expressive genetic progresses with the selection. The correlation estimates between the growth and production with the technological wood characters indicating the absence of genes pleiotropics in the control of ones and the expected small genetic progresses for the indirect selection.
Genetics parameters for growth, yield and wood technological characters in Eucalyptus spp. clones
Keywords: Forest improvement; Genetic control; Wood quality; Genetic variations; Wood characters; Forestry; Genetic engineering; Plants (botany); Pulp; Viscosity; Wood; Genetic Engineering; Plants; Pulps; Wood Properties